2021
DOI: 10.1371/journal.pone.0249005
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccine effectiveness against influenza A in children based on the results of various rapid influenza tests in the 2018/19 season

Abstract: During influenza epidemics, Japanese clinicians routinely conduct rapid influenza diagnostic tests (RIDTs) in patients with influenza-like illness, and patients with positive test results are treated with anti-influenza drugs within 48 h after the onset of illness. We assessed the vaccine effectiveness (VE) of inactivated influenza vaccine (IIV) in children (6 months–15 years old, N = 4243), using a test-negative case-control design based on the results of RIDTs in the 2018/19 season. The VE against influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Although children aged 6-11 months are included in the recommended group, the vaccine effectiveness (VE) for this specific age group has not been proved recently. Our series of VE studies since the 2013/14 season [7] , [9] , [10] , [11] , [12] , [13] demonstrated that vaccines in younger (6–11 months) and older (6–15 years old) children tended to be less effective. We showed significant VE against influenza A in the 2018/19 season for children aged 6–11 months (63% [95% confidence interval (CI), 15–84]) [7] , but the VE for this age was not statistically significant against either influenza A and B in other seasons (95%CI of the odds ratio included 1.0).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Although children aged 6-11 months are included in the recommended group, the vaccine effectiveness (VE) for this specific age group has not been proved recently. Our series of VE studies since the 2013/14 season [7] , [9] , [10] , [11] , [12] , [13] demonstrated that vaccines in younger (6–11 months) and older (6–15 years old) children tended to be less effective. We showed significant VE against influenza A in the 2018/19 season for children aged 6–11 months (63% [95% confidence interval (CI), 15–84]) [7] , but the VE for this age was not statistically significant against either influenza A and B in other seasons (95%CI of the odds ratio included 1.0).…”
Section: Introductionmentioning
confidence: 79%
“…Our series of VE studies since the 2013/14 season [7] , [9] , [10] , [11] , [12] , [13] demonstrated that vaccines in younger (6–11 months) and older (6–15 years old) children tended to be less effective. We showed significant VE against influenza A in the 2018/19 season for children aged 6–11 months (63% [95% confidence interval (CI), 15–84]) [7] , but the VE for this age was not statistically significant against either influenza A and B in other seasons (95%CI of the odds ratio included 1.0). In one of our studies in the five-season analysis (2013/14–2017/18) [13] , all age groups (1–2, 3–5, 6–12 years old) except 6-11 months showed significant VE for both influenza A and B.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Also, in Japan, patients need the certification of the RIDT results, regardless that they are positive or negative, to go to work or be on sick leave when they have colds during the influenza pandemic season. Therefore, Japanese clinicians routinely use RIDTs as a complementary exam with influenza-like illnesses, and most positive patients are treated with anti-influenza drugs [ 2 ]. Doctors also tend to depend on RIDTs because there are few specific physical findings to influenza [ 3 ].…”
Section: Introductionmentioning
confidence: 99%